Monitoring of quality in health care using indicators - Poldrugovac, Mircha (Medicine, law & society, 2017)
A number of stakeholders identified the need to revise the national set of quality indicators. The objectives of monitoring quality indicators that were determined in 2010 for the most part were not accomplished. Key reasons include: insufficient communication between stakeholders after the indicator set was introduced, insufficient definition of human and financial resources necessary for indicators' monitoring, lack of a thorough ICT structure that could support indicators' monitoring and weak leadership for these activities. A new performance indicators' set requires a clear identification of the objectives to be pursued and consequently of the theoretical framework for the indicators. Mostly it is necessary in addition to the identification of the challenges so far, to also recognize what are the possibilities to strengthen this area in the future.
Keywords: efficiency; health care; health promotion; quality